INFRASTRUKTUR MATERIAL PADA KEARIFAN LOKAL MASYARAKAT DALAM PENGELOLAAN HUTAN DI DESA PA’AU KABUPATEN BANJAR - Rahmawati, Rahmawati; Asysyifa, Asysyifa; Hafizianoor, Hafizianoor (Universitas Lambung Mangkurat, 2024)
Pa'au Village is one of the villages in the Meratus Mountains which is inhabited by the Banjar people who still have descendants from the Dayak Kayutangi tribe. The people in Pa'au Village are very dependent on the forest, on average their livelihoods are farmers, farm labourers. by utilizing the forest for farming, gardening and hunting. The importance of forests for socio-economic life is increasingly recognized, because cultural values in the form of human wisdom in managing nature are considered the best way to manage nature. This study aims to explore the infrastructure aspects of local community wisdom in forest management in Pa'au Village. Data collection was carried out through field observations and interviews. Respondents were identified through a purposeful sampling method. Data processing is carried out through inductive qualitative analysis, which can provide a thorough and thorough understanding of the actual situation. Based on the findings of a study on the wisdom of the local community in forest management in Pa'au Village, the people in farming use the